Sobre los mitos políticos "Roma. El mito político", de Florencio Hubeñák. Ediciones Ciudad Argentina, Buenos Aires, 1997. 481 págs. - Piñeiro, Elena (1997)
Fil: Piñeiro, Elena. Pontificia Universidad Católica Argentina; Argentina